Las guerras de Aljazeera - Atitar de la Fuente, Mokhtar (Historia y Comunicación Social, 2005)
This article analyzes the Aljazeera’s role and the relations between the arabic channel and fighting parts in three armed conflicts: Palestinian second Intifada; the war against the terrorism since 11 september attacks; and the war in Iraq.